Therapy-Induced Electrophysiological Changes in Primary Progressive Aphasia: A Preliminary Study - Stalpaert, Jara; Standaert, Sofie; D’Helft, Lien; Miatton, Marijke; Sieben, Anne; Van Langenhove, Tim; Duyck, Wouter; van Mierlo, Pieter; De Letter, Miet (Frontiers in Human Neuroscience, 2022)
Aims: This preliminary study aimed to investigate therapy-induced electrophysiological changes in persons with primary progressive aphasia (PPA). The investigated event-related potential (ERP) components associated with language processing were the mismatch negativity, P300, N400, and P600. Method: A linguistic ERP test battery and standardized language assessment were administered in four patients with PPA of which two received speech-language therapy and two did not receive therapy. The battery was administered twice with approximately six months in between in each patient. The results of the follow-up assessments were compared to the results of the initial assessments. Results: Although the results of the behavioral language assessment remained relatively stable between the initial and follow-up assessments, changes in the mean amplitudes, onset latencies, and duration of the ERP components were found in the four patients. In the two patients that did not receive speech-language therapy (SLT), an increased delay in 50% and a decreased mean amplitude in 25% of the measured ERP components were found. The electrophysiological changes found in the patients that received SLT were variable. Interestingly, the mismatch negativity and the N400 effect elicited by the categorical priming paradigm were less delayed and had an increased mean amplitude at the follow-up assessment in the patient with the nonfluent variant who received SLT. In this patient, the P600 component was absent at the initial assessment but present at the follow-up assessment. Conclusions: Although no clear patterns in electrophysiological changes between patients who received SLT and patients who did not receive SLT were found by our preliminary study, it seems like the SLT induced improvements or compensation mechanisms in some specific language comprehension processes in the patient with the NFV. The results of this study are still preliminary because only four heterogeneous patients were included. Future studies should include larger patient groups of the three clinical variants because the therapy-induced electrophysiological changes might differ depending on the clinical variant and the underlying pathology.